Organising Value Analysis Value Engineering (VAVE) during New Product Development (NPD) - Abdullah, Ainul Farahin; Adesta, Erry Yulian Triblas; Al-Fadhli, Fawaz M.K.H. (Asian Research Publishing Network (ARPN), 2015)
This paper presents one of the methodologies applied during New Product Development (NPD) phase; Value Analysis Value Engineering (VAVE). VAVE can lead to high-quality products which meet customer desires and at the same time increase the operating income requirements for an organisation. The application of VAVE to NPD can enhance the products value by increasing performance without increasing the cost and affecting the quality, saleability or maintainability. A case study has been discussed and an analysis has been made following the fundamentals of VAVE. At the end, results obtained are discussed.